2022
DOI: 10.1136/archdischild-2021-322906
|View full text |Cite
|
Sign up to set email alerts
|

Availability of active therapeutic hypothermia at birth for neonatal hypoxic ischaemic encephalopathy: a UK population study from 2011 to 2018

Abstract: ObjectiveTherapeutic hypothermia (TH) commenced soon after birth for neonatal hypoxic ischaemic encephalopathy (HIE) improves survival and reduces neurodisability. Availability of active TH at the place of birth (Immediate-TH) in the UK is unknown.DesignPopulation-based observational study.SettingUK maternity centres.Patients5 975 056 births from 2011 to 2018.Intervention methodsFor each maternity centre, the year active Immediate-TH was available and the annual birth rates were established. Admission temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
2
4
1
Order By: Relevance
“…Despite various criteria de ning optimal TH in the literature [16] (time to reach an optimal therapeutic temperature [12], or temperature at admission in therapeutic range [17]), and the extension of TH to less severe NE [18], our results of 70.2% of neonates reaching a rectal temperature within optimal range before 6 hr, is in line with data in the literature. In an early study from The Netherlands and Flanders, TH, indicated with "clear presence of perinatal asphyxia followed by neonatal encephalopathy", was started later than 6 hr after birth in 4.8% of infants [16].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Despite various criteria de ning optimal TH in the literature [16] (time to reach an optimal therapeutic temperature [12], or temperature at admission in therapeutic range [17]), and the extension of TH to less severe NE [18], our results of 70.2% of neonates reaching a rectal temperature within optimal range before 6 hr, is in line with data in the literature. In an early study from The Netherlands and Flanders, TH, indicated with "clear presence of perinatal asphyxia followed by neonatal encephalopathy", was started later than 6 hr after birth in 4.8% of infants [16].…”
Section: Discussionsupporting
confidence: 89%
“…Data using the UK national neonatal research database have allowed to describe more precisely factors associated with delayed timing [17]. The higher proportion of adequate delay among neonates born in a CC versus a non-CC observed in our study (79.7% vs 63.8%) was also reported in the United Kingdom with a higher rate of neonates achieving optimal therapeutic temperatures at admission among those with access to immediate TH in CC versus infants born in a non-CC (83.5% vs 73.7%) [12].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations